Education as a promoter of Physical Activity - Gošnik, Jelka (Array, 2010)
Regular physical activity is an important issue since early age: the habits gained in childhood and youth have a lot of influence on the behavior and the quality of living in adult life. In the promotion of a healthier approach to living, informing young people is of big importance. The research was done among student population in High educational systems, exploring their declarative knowledge on the subject, and showed insufficient level of knowledge in physical and health culture. The implementation of theoretical and practical education results in increased knowledge and active participation. The objective of this research was to determine the stance of the students towards the acquirement of theoretical knowledge in the area of PE. The research gathered 796 students of University of Zagreb. The results show the average, standard deviation and t-test for independent samples. 59, 7% of students declared they only find exercising important, 36, 8% wish to attend both lectures and exercises, and 3, 4% wish to attend only lectures. Interestingly, 8% more of female students declared they wish to have lectures PE. Students were answering the questions concerning the areas they wish to know more about by filling out a multiple choice questionnaire with the spread of five given answers, all of different levels of value (from extremely unimportant to extremely important). The results show that students wish to know more about: proper performance of exercises and individual exercising throughout the life, healthy diet and decreasing body weight, the importance of exercising in preserving good health and illness prevention. The t-test showed the statistically significant difference (p<.01) between the female and male students concerning certain areas. The research also showed that there is a interest and need of implementation of interdisciplinary, theoretical lectures in PE. The assumption is that it would also increase the interest and motivation for regular physical activity.